Strategy development for pt kdl as a service company to anticipate potential demand from 35.000mw government program - Windu Adlis, Adria; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2016)
Abstract — PT KDL has three business lines, the Electricity Business, Electricity Services Business, and Oil & Gas Business. Since its establishment in 1996 up until today, PT KDL rely its revenue source heavily on the Electricity Business. Over 86% revenue of PT KDL comes from the Electricity Business. Another two business lines were never really have a high contribution to PT KDL’s revenue. In May 2015, Indonesian government launched the 35.000 MW Electricity Infrastructure Development Program. Goal of this program is to construct power plants and supporting facilities to add another 35 GW to Indonesian installed capacity in five years. PLN will construct a total of 10 GW power plants in this project, along with its transmission and distribution system. Another 25 GW will be handled to private parties through Independent Power Producer (IPP) scheme. This program will require USD 80 billion capital and expected to have around 40% national content. Face a situation where the Electricity Service Business needs to grow and seeing that the 35.000 MW may offer opportunities, PT KDL should develop a strategy for the Electricity Service Business so it could grow and get new customers, as well as anticipating the opportunity created by the government program. The strategy then developed using Business Model Canvass platform which consist of nine building blocks of a business model. This platform is then also used to analyze current business situation and identify gaps between the proposed strategy and current condition of the business. This strategy gap then delivers an action plan that PT KDL should take to make the Electricity Services Business grow and ready to participate in the 35.000 MW program. The action plan covers both marketing area and operational area. Action plans in marketing required PT KD to establish marketing and customer relation function, create marketing database, identify gap of competencies, conduct direct marketing activity, create a dedicated website, and build partnership with power plant EPC contractors. In operational area, the action plan requires PT KDL to establish a work scheduling and planning function, creating warranty and claim management sytem, implementing work management system, and quality assurance and control, analyzing cost structure, partnership with material suppliers, identify all required documents, and organizing routine training and workshop. Keywords: Business Model Canvass, Strategy, Electricity Service Business, 35.000MW